Caractérisation, continuités et discontinuités des manifestations graphiques des sociétés préhistoriques, proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) : volum 3 : session XXVIII-4 - Paillet, Elena; Sepúlveda R., Marcela; Robert, Éric 1979-; Paillet, Patrick 1961-; Mélard, Nicolas (Archaeopress Archaeology, 2020)
This volume presents the proceedings of Session XXVIII-4 of the XVIII UISPP World Congress (4-9 June 2018, Paris, France), 'Caractérisation, Continuités et Discontinuités des Manifestations Graphiques des Sociétés Préhistoriques.' Papers address the question of exchange and mobility in prehistoric societies in relation to the evolution of their environments through the prism of their graphic productions, on objects or on walls. This volume offers the opportunity to question their symbolic behaviours within very diverse temporal, chrono-cultural or geographic contexts. It also provides the framework for a discussion on cultural identity and how this was asserted in the face of environmental or social changes or constraints
"Available both in print and Open Access"--Homepage. - Conference proceedings. - Also issued in print: 2020. - Includes bibliographical references
Keywords: Art, Prehistoric / Congresses; Antiquities, Prehistoric / Congresses; Kunst; Paläolithikum; Felsbild; Beinschnitzerei; Magdalénien; Konferenzschrift -- 2018 -- Paris